PENGEMBANGAN PENILAIAN HOTS DALAM PEMBELAJARAN MAHᾹRAH ISTIMᾹ’ PADA BUKU BAHASA ARAB MI KELAS VI KEMENTERIAN AGAMA RI - Sayuti, Muhammad (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
Assessment of learning Arabic is often not right on target and seems very monotonous, resulting in output that makes students fail to think at a high level. This study aims to present a new form in the assessment of learning Arabic with the output of increasing students' high-order thinking skills with a holistic learning style. In the process of implementing this research is a qualitative research with the type of document or text study. Data analysis was carried out in four stages, namely data collection, data reduction, data presentation, and finally drawing conclusions. Furthermore, the data presentation in the form of assessment findings on maharah istima' learning is presented in narrative and pictorial form. Presentation of data is done to draw conclusions. The results of this study indicate that the assessment of learning istima' in class VI Arabic books published by the 2020 KSKK Ministry of Religion of the Republic of Indonesia is very monotonous and does not lead to the objectives of learning Hots.